1993
DOI: 10.1159/000201030
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelin and Platelet-Activating Factor in Indomethacin-lnduced Gastric Mucosal Injury in Rats

Abstract: The current study was designed to investigate the role of two potent vasoactive substances, endothelin (ET) and platelet-activating factor (PAF), in the pathogenesis of indomethacin-induced gastric lesions in rats. Treatment with anti-ET antibody before indomethacin administration resulted in a significant decline in the total length of the lesions as determined by gross evaluation. In contrast, CV-6209, a specific PAF antagonist, had no effect on the total length of the lesions. The results strongly suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The role of ET-1 in the pathogenesis of gastric mucosal injury remains an active area of investigation, and over the years several mechanisms of its damaging action have been found, including generation of free radicals, upregulation of platelet-activating factor (PAF) formation, and perturbations of calcium channel and phospholipase C activation (1,11,(15)(16)(17)(18). Moreover, it has been shown recently that ET-1 stimulates the biosynthesis of the proinflammatory cytokine TNFa (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ET-1 in the pathogenesis of gastric mucosal injury remains an active area of investigation, and over the years several mechanisms of its damaging action have been found, including generation of free radicals, upregulation of platelet-activating factor (PAF) formation, and perturbations of calcium channel and phospholipase C activation (1,11,(15)(16)(17)(18). Moreover, it has been shown recently that ET-1 stimulates the biosynthesis of the proinflammatory cytokine TNFa (7).…”
Section: Discussionmentioning
confidence: 99%
“…A mong early signs of gastric mucosal injury associated with the use of nonsteroidal anti-inflammatory drugs (NSAIDs) or the development of stress ulcers in critically ill patients are mucosal ischemia and the disturbances in endothelium-dependent vasoactive substances, nitric oxide, and endothelins (1)(2)(3)(4). These two types of cell signaling molecules are widely distributed throughout the vascular and nonvascular tissues and often exert opposing effects on the physiologic and inflammatory processes mediated by regulatory cytokines (5)(6)(7).…”
mentioning
confidence: 99%
“…Submucosal injection of endothelin‐1 into the rat gastric body induces gastric ulceration 15 . Animal studies have also shown that indomethacin causes reduced mucosal blood flow but that pre‐treatment with anti‐endothelin antibody causes a significant reduction in the size of the subsequent lesion 13 . In vitro studies on human smooth muscle cells have shown that bosentan competitively antagonizes the binding of endothelin‐1 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animals have suggested that indomethacin‐induced gastric mucosal injury may be produced by vasoconstriction mediated via endothelin 13 –15 . Endothelin‐1 (ET‐1), the most potent endogenous vasoconstrictor known, acts directly on smooth muscle, inducing an extremely long‐lasting vasoconstriction 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the vaso constrictive property of ET appears to balance the effect of relaxing factors. Imbalance between the relaxing and contracting factors may contribute to microcirculatory disturbance, leading to tissue injury [9], Previously, we showed an important role of imbalance between ET and PGL in the gastric mucosal injury in an experimental ulcer model induced by indomethacin in rats [17]. Al though evidence to support the involvement of ET in isch emia-reperfusion injury has been reported based on the studies of the coronary and renal circulations [18,19], the role of endogenous ET in hemorrhagic shock-induced gas tric mucosal injury has not been evaluated so far.…”
Section: Discussionmentioning
confidence: 99%